Exploring the Construction of Professional Selves of Non-native EFL Teachers at a Saudi Arabian University - Ahmad, Hussain; Fatmawati, Latada; Shah, Sayyed Rashid; Muhammad Nubli, Abdul Wahab (AWEJ.org, 2017)
This study aims to investigate the factors that develop the professional identity of Pakistani English as a foreign language (EFL) teachers in Saudi Arabia. This study is unique in the sense that there has been hardly any systematic investigation that has considered the professional identity of Pakistani EFL teachers in Saudi Arabia. This study has two considerations: the way EFL teachers' selves evolve and the personal, professional, social and pedagogical factors constructing a teacher’s professional identity. This study was conducted at the English Language Institute of Saudi Arabian University and the study employed a quantitative survey method. The quantitative data was collected from 41 Pakistani EFL teachers by using an online questionnaire. The findings from the research revealed that a number of intrinsic and extrinsic factors develop the professional identity of Pakistani EFL teachers. Among these factors are the participants' pre-Saudi Arabia lives and the decision to become EFL teachers, the decision to come to Saudi Arabia, the impact of their overseas EFL experience, and the social influence on their own professional identity. Moreover, other factors that develop these teachers' professional identities are: being non-native, their views on continuing professional development (CPD), interaction with other EFL teachers, and their professional futures.